EFEKTIFITAS PEMAKAIAN MESIN BOR PADA HOME INDUSTRI - mohd Ridwan (Jurnal Pengabdian Vokasi, 2021)
[Effectiveness of Use of Production Machines in Home Industry] Increasing the quality of production at home industry is very much needed with the use of appropriate tools or auxiliary machines. There are dozens of large, medium and small scale home industries in Magelang, Central Java. The development of production machines is directed at increasing the productivity capacity and quality of home industry products, especially steel/metal product home industry, based on local content and with local and export market shares. the field shows that the use of the right production machines will affect the increase in productivity and production quality. Research by using a sitting drill machine sample and comparing it with hand drill machine users used by the previous home industry, with various production materials from brass and cast iron, showed significant results where productivity looks optimal at 3500 rpm engine speed which is 202%, and production time is much shorter. The difference in working time in hand drilling is an average of 34.3 seconds longer than the sitting drill machine. Good hole results are in the range of 2400 to 2550 rpm